TINJAUAN HUKUM ASURANSI KENDARAAN BERMOBIL - HERNANDA, MUHAMMAD NOOR (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ The implementation of insurance policy of motor vehicle is based on the Act No. 40 of 2014 concerning to insurance and refers to the Financial Service Authority (OJK) in Circulation No. SE-06/D.05/2013 concerning to the Determining of premium rate. The insurer will provide the insured the compensation as determined in policy. The low consequence of insurer who did not pay the claim will get the sanction such as warning, limitation of business activity and the withdraw of business permit. The procedure of claim by provide the real information about the causal factor of accident, submit the identity of driver, and explanation letter from police if there is lost.Keywordes : Insurance, Motor vehicles,